COMPREHENSIVE SYSTEM FOR EVALUATING MECHANISMS FOR MAKING EMERGENCY MANAGEMENT DECISIONS IN THE IT INDUSTRY IN CONDITIONS OF UNCERTAINTY - SHAFORENKO, Igor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a comprehensive analysis of the features of making emergency management decisions in the Ukrainian IT industry under conditions of growing uncertainty caused by martial law and dynamic changes in the technological landscape. Based on a critical analysis of the theoretical work of world-renowned scientists (M. Alle, D. Kahneman, G. Simon) and domestic scholars, it is substantiated that classical models of rational choice are insufficient to describe real-world management practice. It is demonstrated that the effectiveness of crisis decisions directly depends on management’s ability to combine flexibility, adaptability, and a solid analytical basis, which necessitates an interdisciplinary approach to the problem. A survey of employees at Ukrainian IT companies identified the key obstacles they face: a lack of information (indicated by 51.0% of respondents), unformulated goals (25.0%), and a psychological barrier in the form of a fear of making mistakes (12.5%). It was found that responsibility for decision-making in the IT sector is primarily placed on the individual (60.4% of respondents), which emphasizes high individual involvement. In comparison, automated systems are almost not used as the primary tool (2.1%). It was found that in war conditions, the most popular technological tools were cloud technologies (16.7%), machine learning and AI (14.6%), and real-time data analysis (12.5%), indicating an orientation towards the stability and continuity of business processes. The general analysis revealed that decision-making occurs in conditions of moderate and high uncertainty, and the primary factors that help maintain composure are prior experience and a precise algorithm of actions. It was concluded that to increase the resilience of the IT sector, it is necessary to implement comprehensive systems that would integrate both technological tools and subjective factors, such as stress resistance and professional experience. The results obtained provide an empirical basis for developing practical training and methodologies that aim to strengthen the economic security of enterprises.